Challenges for commercialization of university research for agricultural based invention - Yaakub, Noor Inayah; Wan Hussain, Wan Mohd Hirwani; Ab Rahman, Mohd Nizam; Zainol, Zinatul Ashiqin; Mujani, Wan Kamal; Jamsari, Ezad Azraai; Sulaiman @ Mohamad, Adibah; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
This study analyses the challenges for the commercialization of university research for agricultural based invention. It aims at promoting the commercialization of agricultural based research to compete with the existing inventions. From the discussion, it shows that the commercialization of agricultural based invention of university research usually takes a longer time to be marketable, when compared to inventions by agencies such as MARDI and FAMA. The article implies that agricultural based invention of university research should be considered as a significant tool for economic growth. It suggests that a case study and a quantitative analysis will be useful to further formulate propositions and to learn the agricultural based invention of university research.